Contemporary Africa and the foreseeable world order - Onditi, Francis, 1981-; Ben-Nun, Gilad; D'Alessandro, Cristina; Levey, Zach; Bah, Abu Bakarr, 1969- (Lexington Books, 2019)
Contemporary Africa and the Foreseeable World Order brings together rich and diverse contributions from seasoned scholars from around the globe. Anchored in a wide array of disciplinary perspectives, the contributors explore the interesting and complex dynamics at play in Africa's interactions with the rest of the world--Provided by publisher.